2023
DOI: 10.1111/nyas.15053
|View full text |Cite
|
Sign up to set email alerts
|

The Global Diet Quality Score is associated with nutrient adequacy and depression among Vietnamese youths

Phuong Hong Nguyen,
Lan Mai Tran,
Nga Thu Hoang
et al.

Abstract: The Global Diet Quality Score (GDQS) has been recommended as a simple diet quality metric that is reflective of both nutrient adequacy and noncommunicable disease outcomes. It has been validated among women of reproductive age (15–49 years) in diverse settings but not specifically among younger women. This paper examines the relationship between the GDQS and nutrient adequacy, anthropometric outcomes, and depressive symptoms among 1001 Vietnamese young women aged 16–22 years. In energy‐adjusted models, the GDQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Workers tended to consume significantly lower proportions of fast foods, instant noodles, or baked/grain‐based sweets than students but a higher proportion of other unhealthy items (soft drinks, sweets, processed meats) 21 . Second, with reference to mental health, we found a significant association between diet quality as measured by the GDQS and behavioral health/depression 22 . These two findings, taken again below, offer insights on how factors such as these should be considered when designing nutritional behavior change interventions.…”
Section: Summary Findingsmentioning
confidence: 51%
See 3 more Smart Citations
“…Workers tended to consume significantly lower proportions of fast foods, instant noodles, or baked/grain‐based sweets than students but a higher proportion of other unhealthy items (soft drinks, sweets, processed meats) 21 . Second, with reference to mental health, we found a significant association between diet quality as measured by the GDQS and behavioral health/depression 22 . These two findings, taken again below, offer insights on how factors such as these should be considered when designing nutritional behavior change interventions.…”
Section: Summary Findingsmentioning
confidence: 51%
“…Vietnam's diets being reasonably diverse, about 60% of AYW achieved minimum dietary diversity for women (at least five food groups) and ate many of the foods categorized as healthy by the GDQS, but intake levels were too low relative to national dietary guidelines. This, combined with the common consumption of unhealthy foods (processed meats, baked sweets, instant noodles) resulted in low GDQS scores, with 32% of the sample classified as moderate and 23% as high risk of poor‐quality diets and related NCD outcomes 22 . Similar to the findings in Medellin, the Optifood analysis for the Vietnam sample found that improving nutrient intake based solely on local foods would be challenging.…”
Section: Summary Findingsmentioning
confidence: 69%
See 2 more Smart Citations